Legal Position of Rights to Traditional Land Owned by the Batak Toba Community in North Tapanuli Regency, Reviewed from the Perspective of Indonesian Positive Law - Simanjuntak, Faticepul LF. (Formosa Journal of Science and Technology, 2024)
The Toba Batak hold customary land. Will, but in practice, the range of customary rights has shrunk owing to control and takeover by other parties. The takeover has caused economic challenges for the Toba Batak people, who are unable to use their land and woods to support their daily necessities. This position contradicts Article 3 of the LoGA, which provides that the State expressly acknowledges the existence of ulayat rights and comparable rights derived from the customary law community as long as they exist in fact. The statute is endorsed by the Minister of Agrarian Affairs/Head of BPN Regulation 5 of 1999, which establishes guidelines for the settlement of Ulayat Rights Issues in the Indigenous statute Community. The research technique in this paper is descriptive, with an empirical legal approach. Data was gathered via collecting both primary and secondary data. Primary data was acquired through interviews with informants. Secondary data is gathered from both main and secondary legal documents. Document studies and interviews were utilized as data gathering tools in this study, and the results were examined qualitatively. Thus demonstrating that lands have become commodities that may be traded at any moment, as occurs in metropolitan areas, and that the mystical religious significance of the land has shifted to economic (commercial) value. This also demonstrates that individuals are more prepared to hold land separately from the land (ripe-ripe), allowing the land to be exchanged. BAL emphasizes the need of land registration in order to shift the emphasis of legal certainty via verification of rights in paper to the unwritten character of traditional customary law.